Revolutions in international law : the legacies of 1917 - 1917: Revolution, Intervention and International Law(s) (Conference) (2017 : Melbourne, Vic.).; Greenman, Kathryn; Orford, Anne; Saunders, Anna, 1988-; Tzouvala, Ntina (Cambridge : Cambridge University Press, 2021)
In 1917, the October Revolution and the adoption of the revolutionary Mexican Constitution shook the foundations of the international order in profound, unprecedented and lasting ways. These events posed fundamental challenges to international law, unsettling foundational concepts of property, statehood and non-intervention, and indeed the very nature of law itself. This collection asks what we might learn about international law from analysing how its various sub-fields have remembered, forgotten, imagined, incorporated, rejected or sought to manage the revolutions of 1917. It shows that those revolutions had wide-ranging repercussions for the development of laws relating to the use of force, intervention, human rights, investment, alien protection and state responsibility, and for the global economy subsequently enabled by international law and overseen by international institutions. The varied legacies of 1917 play an ongoing role in shaping political struggle in the form of international law.
International law international law and revolution : 1917 and beyon / Kathryn Greenman, Anne Orford, Ntina Tzouvala and Anna Saunders -- Looking eastwards : the Bolshevik theory of imperialism and international law / Ntina Tzouvala and Robert Knox -- Lenin at Nuremberg : anti-imperialism and the juridification of crimes against humanity / Amanda Alexander -- Excluding revolutionary states : Mexico, Russia and The League Of Nations / Alison Duxbury -- Law, class struggle and nervous breakdowns / Mai Taha -- Microcosm soviet constitutional internationality / Scott Newton -- Law and socialist revolution : early soviet legal theory and practice / Owen Taylor -- Intervention : sketches from the scenes of the Mexican and Russian revolutions / Dino Kritsiotis -- Mexican revolutionary constituencies and the Latin American critique of us intervention / Juan Pablo Scarf -- Mexican post-revolutionary foreign policy and the Spanish civil war : legal struggles over intervention at the league of nations / Fabia Fernandes Carvalho Veçosos -- 1917 : property, revolution and rejection in international law / Kate Miles -- 1917 and its implications for the law of expropriation / Daria Davitti -- Contestations over legal authority : the Lena Goldfields Arbitration 1930 / Andrea Leiter -- The Mexican revolution : alien protection and international economic order / Kathryn Greenman -- Animated by the European spirit' : European human rights as counterrevolutionary legality / Anna Saunders -- Human rights, revolution and the 'good society' : the Soviet Union and the universal declaration of human rights / Jessica Whyte.
Title from publisher's bibliographic system (viewed on 29 Jan 2021).
Keywords: Revolutions -- History -- 20th century -- Congresses; Legitimacy of governments -- Congresses; Recognition (International law) -- Congresses; Soviet Union -- History -- Revolution, 1917-1921 -- Law and legislation -- Congresses; Mexico -- History -- Revolution, 1910-1920 -- Law and legislation -- Congresses